(untitled) (Mustansiria Dental Journal, 2018)
Oral cancer is a major public health issue worldwide; it remains a highly lethal and disfiguring disease. in Iraq little is written regarding the occurrence of oral cancer. The aim of this study is To examine the effect of smoking oral mucosa cytological. Hundred men aged between 40 and 70, comprising 50 smokers and 50 non smokers. Material for exfoliative cytology was collected with a metal spatula from the lateral border of the patient’s tongue and from the floor of the mouth and the samples were then submitted for Papanicolaou staining. Then cytologic smears were classified according to Papanicolaou’s classification. the results of the current study reveals that there is a significant association between smoking (number of cigarette smoked per day and the duration of smoking (year) and the occurrence of cytological changes in the oral mucosa ,p <0.001.and there is a significant association between the age and the papanicolaou’s classes ,p<0.001. .